Using participatory design in the development of a language learning tool - Zaphiris, Panayiotis; Constantinou, Penelope (My University, 2007)
Purpose This paper aims to demonstrate how participatory design methodologies can be used for the design of inter- active learning tools for children. Design/methodology/approach This paper presents the methodology employed for the design of a multimedia tool for teaching Greek to young children aged 6 to 12. The preliminary data collection included interviews, questionnaires and observations, whereas the actual design of the tool was carried out using a Participatory Design methodology which advocates a design approach that focuses on the intended user of the service or product, emphasising the active involve- ment of users throughout the design process. Findings The paper provides detailed information from each of the data collection techniques used. It also highlights the successes and difficulties in implementing participatory design in an e-learning context. Originality/value Although participatory design has been used in the design of other systems, it is rarely used as the design framework of learning applications. So the paper expands ones knowledge of implementing participatory design methodologies in learning.
Keywords: Design; Communication technologies; Children (age groups); E-learning; Language; Learning